Premenstrual Disorders (PMS and PMDD) Incidence, and its Predictors in Iranian Medical University Students; An Exploratory Cross Sectional Study: PMS incidence and its predictors in medical students - Miraj, Sepideh; Derakhshani, Maryam; Mohammadbeigi, Abolfazl; Hassanzadeh, Fatemeh; Ramezani, Fatemeh; Aligol, Mohammad (Ethiopian Journal of Reproductive Health, 2023)
Introduction: Premenstrual disorders are a wide range of physical, behavioral, and psychological symptoms which emergence before menstruation and in the first initial days of menstruation which repeat in several cycle. This study aimed to evaluate the Premenstrual syndrome (PMS) and Premenstrual dysphoric disorder (PMDD) incidence and its related factors among Iranian medical students. Materials and Methods: In a is cross sectional study 264 students of Qom university of Medical Sciences were selected by stratified proportional to size and simple random sampling method. Demographic form, Premenstrual Symptoms Screening Tool (PSST) and Daily Record of Severity of Problems (DRSP) questionnaires were used for data collection and evaluation of subjects for PMS and PMMD according to the DSM-IV criteria. Data analysis conducted using SPSS version 20 (SPSS Inc., Chicago, IL, USA) by Chi square, independent t-test and multivariable logistic regression. P value lower 0.05 was considered as significant. Results: The mean age of subjects was 21.05±2.20 years and 102 students (38.6%) were diagnosed as PMS that 8% (21 subjects) were labeled as PMMD. Decreased interest in daily activities (60.6%), depressed mood (60.2%), fatigue/lack of energy (52.3%), physical symptoms and difficulty concentrating (51.1%) were the most common PMS symptoms. Bivariate analysis showed that BMI, marital status, chronic disease history, and continuous use of medication have significant relationship with PMS morbidity. Marriage 2.1 (OR=2.1, 95% CI: 1.12-4.42) and stress in the last 3 months (OR=2.38, 95% CI: 1.23-4.63) were two most important predictors of PMS in medical students based on multivariate logistic regression. Conclusion: Decreasing the students stress, especially in students with chronic disease history that have continuous medication consumption could be effective factors for control the PMS symptoms. Moreover, educational stress beside higher familial stress in married students due to socioeconomic and cultural factors, are the related predictive determinants of PMS. Change in life style by rest taking and enough sleeping, and counseling could be help the affected subjects.